Trade complementarity and intra-industry trade between MERCOSUR and its main European Partners during 1991-2012: What does the evidence suggest? - Jacobo, Alejandro D. (2015)
Fil: Jacobo, Alejandro D. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.